Zebrafish prox1b Mutants Develop a Lymphatic Vasculature, and prox1b Does Not Specifically Mark Lymphatic Endothelial Cells - Tao, Shijie (Public Library of Science, 2011)
BACKGROUND: The expression of the Prospero homeodomain transcription factor (Prox1) in a subset of cardinal venous cells specifies the lymphatic lineage in mice. Prox1 is also indispensible for the maintenance of lymphatic cell fate, and is therefore considered a master control gene for lymphangiogenesis in mammals. In zebrafish, there are two prox1 paralogues, the previously described prox1 (also known as prox1a) and the newly identified prox1b. PRINCIPAL FINDINGS: To investigate the role of the prox1b gene in zebrafish lymphangiogenesis, we knocked-down prox1b and found that depletion of prox1b mRNA did not cause lymphatic defects. We also generated two different prox1b mutant alleles, and maternal-zygotic homozygous mutant embryos were viable and did not show any lymphatic defects. Furthermore, the expression of prox1b was not restricted to lymphatic vessels during zebrafish development. CONCLUSION: We conclude that Prox1b activity is not essential for embryonic lymphatic development in zebrafish.